2005
DOI: 10.1016/j.socscimed.2004.05.013
|View full text |Cite
|
Sign up to set email alerts
|

The causes of low back pain: a network analysis

Abstract: Publisher's copyright statement:Additional information: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-pro t purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal perm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 55 publications
3
24
3
Order By: Relevance
“…This is similar to the report that 51.5% nurses with multiple pregnancies experienced LBP [4]. Female participants reported that their back pain was attributed to pregnancy and childbirth [19]. Obesity, which is one of the contributing factors for lumbar pain, leads to decreased abdominal muscle strength and increases the level of lumbar-lordosis.…”
Section: Discussionsupporting
confidence: 84%
“…This is similar to the report that 51.5% nurses with multiple pregnancies experienced LBP [4]. Female participants reported that their back pain was attributed to pregnancy and childbirth [19]. Obesity, which is one of the contributing factors for lumbar pain, leads to decreased abdominal muscle strength and increases the level of lumbar-lordosis.…”
Section: Discussionsupporting
confidence: 84%
“…14,15 Studies have investigated activities, situations, and anatomic structures that people see as being responsible for their back pain, but not how or why beliefs have been formed. 14,[16][17][18] Health care professionals may negatively influence patient beliefs. 19 There is strong evidence that patients' beliefs about low back pain are associated with their clinicians' beliefs, and moderate evidence suggests that patient and clinician fear avoidance beliefs are also associated.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic Low back dysfunction (CLBD) developed as a result of bad postural addiction, spondylolisthesis, spondylosis, repetitive trauma or derangement, the dysfunction syndrome is the condition in which tightness and instability developed causing pain before complete full normal end range movement. Essentially, the condition arises because the movement is performed inadequately at a time when shortening of soft tissues is taking place [4]. The goals of the treatment include reducing pain, improving the quality of life and increase function depending on the type and source of the pain.…”
mentioning
confidence: 99%